Project-oriented teaching during learning ukrainian as a foreign languages: development of students' communication skills - Bidenko, Larysa; Diachuk, Liudmyla; Ghahrodi, Halyna Lotfi; Krymets, Oksana; Cherniavska, Svitlana (Universidad de Carabobo, 2024)
Perception of professional information is possible due to orientation to different sources that are related to foreign language learning. The study aims to determine the peculiarities of the development of communication skills of students through the use of project-oriented teaching of Ukrainian as a foreign language. Ensuring the development of the set purpose was possible due to the use of the methods of analysis, observation and estimated efficiency coefficient, effect level coefficient, Student’s coefficient. Project-oriented approaches to education, oriented to the development of communication skills were developed during the study. They were based on dubbing the disciplines in two languages, formation of theoretical language knowledge, and development of dialogue communication and writing skills. The most positive role of the selected project-oriented teaching was found using SWOT analysis. The practical significance of the work provides for the possibility of the use of developed approaches to studying Ukrainian as a foreign language for the possibility of obtaining communication skills. The perspective of the study will be oriented towards a comparison of the influence of project-oriented studying of students of different ages with consideration of their possibilities at the beginning.

La percepción de la información profesional es posible gracias a la orientación a diferentes fuentes relacionadas con el aprendizaje de lenguas extranjeras. El estudio tiene como objetivo determinar las peculiaridades del desarrollo de las habilidades comunicativas de los estudiantes mediante el uso de la enseñanza orientada a proyectos de ucraniano como lengua extranjera. Asegurar el desarrollo del propósito establecido fue posible gracias al uso de los métodos de análisis, observación y coeficiente de eficiencia estimado, coeficiente de nivel de efecto, coeficiente de Student. Durante el estudio se desarrollaron enfoques educativos orientados a proyectos, orientados al desarrollo de habilidades comunicativas. Se basaban en el doblaje de las disciplinas en dos idiomas, la formación de conocimientos lingüísticos teóricosy el desarrollo de las habilidades de comunicación y escritura en el diálogo. El papel más positivo de la enseñanza orientada a proyectos seleccionada se constató mediante el análisis FODA. La importancia práctica del trabajo prevé la posibilidad del uso de los enfoques desarrollados para el estudio del ucraniano como lengua extranjera para la posibilidad de obtener las habilidades comunicativas. La perspectiva del estudio se orientará hacia la comparación de la influencia del estudio orientado a proyectos de estudiantes de diferentes edades teniendo en cuenta sus posibilidades al principio
Keywords: bilingualism; language knowledge; communication skills; dialogue communication; interactive technologies; active student interaction; bilingüismo; conocimientos; lingüísticos; destrezas comunicativas; comunicación dialogada; tecnologías interactivas; interacción activa de los alumnos